Pengaruh Facilitation Condition terhadap Niat Menggunakan Sistem Informasi Manajemen Hasil Pengawasan (SIM HP) dengan Harapan Usaha dan Harapan Kinerja Sebagai Variabel Intervening (Studi Kasus Pada Inspektorat Provinsi Banten) - Roza Mulyadi; Lili Sugeng Wiyantoro (Universitas Serang Raya, 2018)
This study examines the effect of facilitating conditions and examine how themediating role of business expectations and the expectations of the performance of theintention to use Management Information System Monitoring Results (MIS MR). Thisresearch was conducted at the Institute Inspectorate Banten Province as the research object.In this study a total of 37 questionnaires distributed questionnaires. Of these questionnaireswere not returned the questionnaire amounted to 2, or 5.4%, and totaled 35 questionnaireswere returned questionnaires or 94.6% of respondents who restore, and questionnaires thatcan be processed amount to 35 or 94.6%. Researchers used the test SEM (StructuralEquation Modelling) by using test equipment SmartPLS.This study uses survey research with primary data collection using the questionnaire.The results showed (1) Facilitation Condition positive effect on business expectations (2)Facilitation Condition positive effect on performance expectations (3) Facilitation Conditionpositive effect on Facilitation Condition positive effect on (4) Hope effort has positiveinfluence on the intention to use Management Information System Results Supervision (MISMR) (5) Hope's performance a positive influence on the intention to use ManagementInformation System Monitoring Results (MIS MR) (6) Hope successful attempt to mediateFacilitation Condition intention of using Management Information System MonitoringResults (MIS MR) (7) Hope the performance condition is successfully mediate facilitation ofthe intention of using Management Information System Monitoring Results (MIS MR).